A developmentally regulated chlamydial gene with apparent homology to eukaryotic histone H1. - Perara, E (1992)
We have developed a method for the isolation of genes whose expression is developmentally regulated from the murine strain of Chlamydia trachomatis. Here we describe the identification of two developmental stage-specific genes, one of which is predicted to encode a 26-kDa lysine- and alanine-rich protein that appears to be homologous to several eukaryotic histone H1 proteins. A substantial proportion of this homology relates to its distinctive amino acid composition. No sequence homology was observed between this protein and other bacterial "histone-like" chromosomal proteins, but homology does exist with two other recently described prokaryotic proteins. The protein is expressed late in chlamydial development, during the transition from reticulate bodies to elementary bodies. The basic nature of the protein predicts that it could bind DNA, and Southwestern blotting experiments confirm this finding. These properties are consistent with a role either in the regulation of late gene expression or in the compaction of the chlamydial genome.